Achieving global sustainability : policy recommendations - Sawa, Takamitsu; Iai, Susumu; Ikkatai, Seiji (Sustainability science series, 2011)
"The problem of global sustainability is indisputably the most serious issue facing humanity today. One of the biggest factors in the deterioration of global sustainability is climate change, which has been exacerbated by the entire range of human activities and is inextricably related to modern civilization. Solving this difficult problem requires a drastic redesign of society from all aspects--technological, economic and social. This book looks at how to achieve a more secure level of global sustainability and gathers together a variety of recommendations."--Publisher's description.